دراسة تلوث بعض مناطق مياه الشاطئ السوري وبعض الكائنات الحية البحرية ببعض العناصر المعدنية الثقيلة (Latakia University Journal -Basic Sciences Series, 2018)
يتناول هذا البحث تبعاً لمفهوم تعاظم السلسلة الغذائية موضوع تلوث المياه الشاطئية والكائنات الحية البحرية بالعناصر المعدنية الثقيلة (Cd, As, Pb, Zn, Cr, Cu)، مروراً بالعوالق النباتية والحيوانية، القاعيات، الأسماك وانتهاءً بالإنسان الذي يمثل أعلى قمة هرم السلسلة الغذائية. وشملت الدراسة بعض أنواع ثنائيات المصراع   Brachidonta variabilis, Pinctada radiate,, Malleus regula decussatus Ruditapes Tellina planate, والأسماك Siganus luridus, Siganus rivulatus, Sardine Mugil, إلى جانب المياه في بعض مناطق الشاطىء السوري، وأبدت النتائج ارتفاعاً ملحوظاً في تراكيز العناصر المدروسة في الكائنات البحرية المدروسة بالمقارنة مع المياه، وهذا يفسر ظاهرة الخواص التراكمية للعناصر المعدنية ضمن النسج اللحمية للكائنات الحية البحرية. أظهرت النتائج أيضاً ارتفاعاً ملحوظاً في تراكيز العناصر في القاعيات سابقة الذكر بالمقارنة مع عينات الأسماك نظراً لما تتمتع به هذه القاعيات من خاصية ترشيح المياه، وبمقارنة النتائج التي تمَّ الحصول عليها مع نتائج لدراسات أجريت في حوض المتوسط لبعض الأنواع المدروسة نفسها، لوحظ انخفاض في تراكيز العناصر (Cd, As, Pb, Cr, Cu) وتقارب إلى ارتفاع في تركيز عنصر التوتياء. This research deals with the subject of pollution of the Syrian coastal water and marine organisms by heavy metals (Cd, As, Zn, Pb, Cr, Cu)  according to the magnification concept of food-chain, passing by Phytoplankton and Zooplankton, Benthos, Fish and finally by man is at the top of the food-chain pyramid. This study included some sorts of bivalvia (Brachidonta variabilis, Pinctada radiate,, Malleus regula, Ruditapes decussates, Tellina planate) and fish (Mugil, Siganus luridus, Siganus rivulatus, Sardine)  in addition to water samples in some Syrian coast zones. The results showed high concentration of studied elements in the studied marine organisms compared with water samples. This explains the phenomenon of accumulation properties of metals in the flesh tissues of marine organisms. The results also showed a noticeable high concentration for elements in the studied zoobenthos compared with fish samples, since it has the water-filtration property. On the other side, by comparing the results of this research with the results of other studies of the same sort in the Mediterranean basin, we observed a decrease in the concentration of  (Cd, As, Pb, Cr, Cu) elements, and an increase in the concentration of zinc element.